Assessment of the risk of injury to athletes in connection with psychophysiological indicators (skiing) - Fedorchuk, S.; Lysenko, O.; Kolosova, O.; Khomyk, I.; Ivaskevych, D.; Tukaiev, S. (Sport Science and Human Health, 2020)
Introduction. In modern sports, a high level of physical performance of the athlete is due to the functional properties and condition of all body systems. Of particular importance is the assessment of the functional state of the central nervous system. At the same time, the potential risk of injuries increases with each passing year, so one of the main tasks of sports physicians, psychologists, physiologists, especially in high-achievement sports, is to reduce injuries in sports.